+0  
 
0
45
1
avatar

(127)^4−x=9^2x−1

 Feb 19, 2020
 #1
avatar+109740 
+1

I think this might be 

 

(127)^(4 - x)  = 9^(2x  -1)     take  the log of both sides

 

log (127)^(4  -x)  = log (9)^(2x -1)    and we can write

 

(4 - x) log (127) = ( 2x - 1) log (9)

 

4log (127) - x log (127)  = 2xlog (9)  -log (9)    rearrange as

 

4log (127) + log (9)  = x [ log (127)  + 2 log (9) ]    

 

x =   [ 4log (127) + log(9) ]  / [ log (127) + 2log (9)  ]   ≈ 2.335

 

 

cool cool cool

 Feb 19, 2020

53 Online Users

avatar
avatar
avatar
avatar